Investigation of English Students’ Learning Strategies in Oracy in an Academic Context Class - Berliana, Winny (International Journal of Science and Society, 2024)
The study aimed to describe the common English students’ learning strategies used in Oracy class at English Department in Universitas Jambi. The participants were English students who have taken Oracy class in 2018/2019 academic year. The total of participants were 6 students from 3 classes (001,002 and 003), there were 2 students from each classes. This study used a qualitative design with case study as an approach. The researcher used interview to find out the data. There were 6 learning strategies: memory, cognitive, affective, metacognitive, compensation and social strategies based on Oxford (1990). The result indicated most students used some strategies in Oracy class. Moreover, in some situations most students need self-efficacy, they also have to use gestures in increasing confident in Oracy class. In addition, they preferred to repeat the new words and then memorized those words. The implication of this study was the students might get the appropriate strategies in Oracy class and for the teachers, it could be the substance of knowledge to know about what students normally did in learning oracy and also found out the way to teach the appropriate strategies to make they got the comprehension in Oracy in Academic Context class, and subsequent researchers could also examine more deeply about what strategies students did in the Oracy class, according to the level of students’ ability.